Edukasi Menstruasi pada Remaja Putri di Pondok Pesantren Darussalam Al-Hafidz Kota Jambi - Ria Febrina (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
Adolescence according to WHO are those who are in the transition phase between childhood and adulthood. According to the Indonesian Minister of Health the age limit for teenagers is between the ages of 10 to 19 years and not yet married. Adolescence or puberty is a stage in development when sexual maturity and reproductive ability are achieved. One sign of a woman entering adolescence is menstruation. Menstruation is a normal process, which occurs every month in almost all women. Menstruation occurs when blood is removed, within 3-5 days each month. There are still teenagers in Asam Atas village who do not know the function of reproduction, PMS symptoms and how to cope with menstrual pain. Poor or wrong menstrual education can be a cause of long-term reproductive health problems. Therefore it is necessary to provide counseling to increase adolescent knowledge about menstruation. It is expected to increase awareness of teenage girl about the need to maintain personal hygiene during menstruation. This community service activity was carried out at the Darussalam Al-Hafidz Islamic Boarding School in Jambi City. The time of implementation in February 2019. The target is teenage girl. Community service methods include a survey and lecture approach. The results obtained are teenage girl able to understand about menstruation and how to cope with pain during menstruation. It is recommended that schools work together with health workers to routinely provide reproductive health education to teenage girl.